Soil Quality Assessment Using Soil Organic Carbon, Total Nitrogen And Microbial Properties In Hilly Agro-Ecosystem (Applied Biological Research, 2018)
Assessment of soil quality is an invaluable tool in determining the sustain ability and environmental impact of agricultural ecosystems. The study was  conducted to assess the quality of soils under traditional cultivation practices,  i.e. shifting cultivation, agriculture practice, forestry plantations of Pinus  kesiya, Alnus nepalensis, Parkia roxburghii, Michelia oblonga and Gmelina  arborea) and modified agro-forestry system of agri-horti-silvi-pastoral system  using soil organic carbon (SOC), soil total nitrogen (STN) and soil microbial  biomass C (SMBC) and N (SMBN) at ICAR Complex for NEH Region,  Umiam, Meghalaya, India. The shifting cultivated areas had the lowest SMBC  value of 192 mg kg-1 while soil under M. oblongaplantation had significantly  (P < 0.05) highest value of 478 mg kg-1. The proportion of SMBC to total soil  organic carbon (SOC) was in the range of 0.9 to 1.9% across all the systems. The forestry plantation soils had higher SMBC and SMBN as a percentage of  SOC and STN respectively than the cultivated arable land soils. The study  suggests that the forestry followed by agri-horti-silvi-pastoral system seems to  be of better option for sustainable crop production with maintenance of soil  quality/health under tropical agro-ecosystems of North-east India.
Keywords: Hilly ecosystem; organic carbon; soil quality; SMBC; SMBN; total nitrogen